Forecasting scenic preferences for urban streetscape using photographic simulation - Othman, Jamilah; Othman, Rashidi (AESS Publications., 2018)
The urban streetscape of Raja Laut is supported with multiple socio-cultural, administrative, educational, and economic activities. As such, awareness for a healthier environment can be promoted by encouraging more community involvement, including public participation in the landscape assessment exercise. It is believed that the charm and rich characters of the non-natural landscape components of the urban streetscape of Raja Laut should be protected, due to their scenic resources. Therefore, this paper documents the public's scenic preferences for future urban streetscape with an aim to identify the landscape components that have potential enhancing the scenic resources. Photographic simulation with small size sampling was used to assess the public's preferences. Interestingly, early findings indicate that colourful streetscape provide high scenic value. The insights also suggest that both natural and man-made attributes have equal scenic importance. Finding further explains the significant influence of natural attribute in the design and planning of the urban streetscapes in Kuala Lumpur and thus, should be further investigated.